Design and implementation of a dual microcontroller-based smart headlight control system using a dynamic load adjustment mechanism - Liew Hui Fang; Rosemizi Abd Rahim; Muhammad Izuan Fahmi Romli; A. A. M. Ezanuddin; Shamshul Bahar Yaakob (International Journal of Power Electronics and Drive Systems (IJPEDS), 2026)
Conventional automotive headlamp systems operate using fixed illumination levels and manual beam levelling, limiting adaptability to dynamic driving conditions such as vehicle load variation, speed changes, and ambient light fluctuations. These static systems may result in reduced visibility, increased glare, and inefficient energy usage. This paper presents a dual microcontroller-based smart headlight control system incorporating a dynamic load adjustment mechanism for real-time regulation of beam intensity and angle. Unlike conventional single-controller configurations, the proposed architecture distributes control tasks between two dedicated microcontrollers to enhance modularity and processing stability. The first controller performs adaptive intensity regulation through speed-dependent low-beam dimming and LDR-based high-beam glare control, while the second controller enables automatic beam levelling using rear suspension load sensing to compensate for vehicle pitch variations. The system was validated through Proteus simulation and hardware prototyping. Experimental results demonstrate low-beam modulation at 30%, 80%, and 100% brightness levels, high-beam voltage control from 0.04 V to 1.82 V, and adaptive beam angle adjustments under varying load conditions. Approximately 90% simulation-to-hardware agreement confirms system reliability. Compared to conventional systems, the proposed design offers improved adaptive illumination, glare mitigation, and energy-aware operation, supporting integration into modern LED-based automotive lighting platforms and electric vehicles.